Development of mini micro injection moulding machine - Daelami, Aminuddin (2012)
The project is to develop a mini micro injection moulding machine. This study consists of three stages which are design concept, fabrication process, and assembly process of the mini micro injection molding that will capable to run similarly as the real industries conventional micro injection molding machine. For the design concepts, two to three injection molding mechanism is designed, compared and choose the best design that can match the requirement of the mini micro injection machine. After the design has been decided, fabrication process will take place. In this project, it is important to define and organize the best and fastest method that suitable to fabricate the machine. Assembly processes need to be done to complete the machine. It consist of assemble the two unit of injection machine which are injection unit and clamping unit. For the last stage, in order to test and function the machine, we need to make it capable to melt the resin plastic and the injection plunger can inject the molten plastic in to the mould cavity through the nozzle.